Role of vertical advection and diffusion in long-range PM2.5 transport in Northeast Asia - Kim, Eunhye; Kim, Byeong Uk; Kang, Yoon Hee; Kim, Hyun Cheol; Kim, Soontae (Environmental Pollution, 2023)
This study quantitatively analyzed the role of vertical mixing in long-range transport (LRT) of PM2.5 during its high concentration episode in Northeast Asia toward the end of February 2014. The PM2.5 transport process from an upwind to downwind area was examined using the Community Multi-scale Air Quality (CMAQ) modeling system with its instrumented tool and certain code modifications. We identified serial distinctive roles of vertical advection (ZADV) and diffusion (VDIF) processes. The surface PM2.5 in an upwind area became aloft by VDIF— during daytime—to the planetary boundary layer (PBL) altitude of 1 km or lower. In contrast, ZADV updraft effectively transported PM2.5 vertically to an altitude of 2–3 km above the PBL. Furthermore, we found that the VDIF and ZADV in the upwind area synergistically promoted the vertical mixing of air pollutants up to an altitude of 1 km and higher. The aloft PM2.5 in the upwind area was then transported to the downwind area by horizontal advection (HADV), which was faster than HADV at the surface layer. Additionally, VDIF and ZADV over the downwind area mixed down the aloft PM2.5 on the surface. During this period, the VDIF and ZADV increased the PM2.5 concentrations in the downwind area by up to 15 μg·m−3 (15%) and 101 μg·m−3 (60%), respectively. This study highlights the importance of vertical mixing on long-range PM2.5 transport and warrants more in-depth model analysis with three-dimensional observations to enhance its comprehensive understanding.
Keywords: Downdraughts; Horizontal advection; Long range transport; Mixing down; Northeast Asia; Particulate Matter; Planetary boundary layers; PM 2.5; Vertical advection; Vertical mixing; Air Pollutants; Air Pollution; Asia; China; Environmental Monitoring; Particulate Matter; Downdraft; LRT; Mixing down; Particulate matter; PBL; Vertical mixing